EMOTION-MOTION INTERACTIONS IN CONVERSION DISORDER: AN FMRI STUDY. Issue 9 (13th August 2015) - Nicholson, Timothy R; Aybek, Selma; O'Daly, Owen; Zelaya, Fernando; Kanaan, Richard A; David, Anthony S
Abstract : Objective: To evaluate the neural correlates of implicit processing of negative emotions in motor conversion disorder (CD) patients compared to healthy controls. We predicted increased amygdala responses in CD patients with a failure to habituate normally. Method: An event related fMRI task was completed by 12 motor CD patients and 14 matched healthy controls using standardised visual stimuli of emotional faces ("Ekman faces") with negative (fearful and sad) emotional expressions. This was compared to faces with neutral expressions. Temporal changes in the sensitivity to stimuli were also modelled and tested in the two groups. Images were acquired with a 3T scanner and analysed using SPM-8 with both 'region of interest' (ROI) analyses on the amygdala and 'whole brain' analyses. Results: We found increased amygdala activation to negative emotions in CD compared to healthy controls in ROI analyses, which persisted over time consistent with previous findings using emotional paradigms. Furthermore during 'whole brain' analyses we found significantly increased activation in CD patients in areas involved in the "freeze response" to fear (periaqueductal grey matter), and areas involved in self-awareness and motor control (superior frontal gyrus and supplementary motor area). Anxiety scores were not significantly different between the two groups. Conclusion: This study provides evidence that CD patients have abnormal emotion regulation with the amygdala becoming relatively more responsive (i.e. sensitized) following repeated exposure to negative emotional cues. Patients with CD also activated midbrain and frontal structures that could reflect an abnormal behavioural-motor response to negative, including threatening, stimuli. This suggests a mechanism linking emotions to motor dysfunction in CD.